Seaweed intake and risk of cardiovascular disease: the Japan Public Health Center–based Prospective (JPHC) Study. Issue 6 (13th September 2019) - Murai, Utako; Yamagishi, Kazumasa; Sata, Mizuki; Kokubo, Yoshihiro; Saito, Isao; Yatsuya, Hiroshi; Ishihara, Junko; Inoue, Manami; Sawada, Norie; Iso, Hiroyasu; Tsugane, Shoichiro; ,
ABSTRACT: Background: The minerals, vitamins, soluble dietary fibers, and flavonoids of seaweed are protective for preventing cardiovascular diseases. However, the association between seaweed intake and risk of cardiovascular disease has not been established. Objectives: We examined the dietary intake of seaweed and its impact upon stroke and ischemic heart disease risk among a Japanese study population. Methods: We surveyed 40, 707 men and 45, 406 women from 2 large cohorts (age range: 40–69 y). Seaweed intake was determined by FFQ at baseline (1990–1994). Incidences of stroke and ischemic heart disease were ascertained until the end of 2009 (Cohort I) or 2012 (Cohort II). Sex-specific cardiovascular disease HRs (95% CIs) were estimated using Cox proportional hazard models after stratification by area and adjustment for cardiovascular disease risk and dietary factors. Results: During 1, 493, 232 person-years of follow-up, 4777 strokes (2863 ischemic stroke, 1361 intraparenchymal hemorrhages, and 531 subarachnoid hemorrhages) and 1204 ischemic heart disease cases were identified. Among men, significant multivariable HRs (95% CIs) for almost daily consumption compared with almost no consumption of seaweed were seen in ischemic heart disease [0.76 (0.58, 0.99); P -trend = 0.04] and total cardiovascular diseases [0.88 (0.78, 1.00); P -trend = 0.08]. Among women, such inverse associations were 0.56 (0.36, 0.85; P -trend = 0.006) for ischemic heart disease and 0.89 (0.76, 1.05; P -trend = 0.10) for total cardiovascular diseases. No significant associations were observed between seaweed intake and risk of total stroke or stroke types among either men or women. Conclusions: Seaweed intake was inversely associated with risk of ischemic heart disease.